Evidence of Recent Active Volcanism in the Balleny Islands (Antarctica) From Ice Core Records. Issue 23 (26th November 2021) - Tetzner, Dieter R.; Thomas, Elizabeth R.; Allen, Claire S.; Piermattei, Alma
Abstract: Volcanism can play a key role in modulating climate; however, a lack of historical records has limited our comprehension of Antarctic volcanism and its role on the cryosphere. Remote sensing can provide insight into active volcanism in Antarctica during the satellite era, although the evidence is often inconclusive. Here, we use independent evidence from ice cores to validate one such potential volcanic eruption from the sub‐Antarctic Balleny Islands in 2001 CE. Multiple ice cores from downwind of the eruption site, record elevated input of sulfate, microparticles, and the presence of tephra, coincident with the eruption. In‐phase deposition of volcanic products confirmed a rapid tropospheric transport of volcanic emissions from a small‐to‐moderate, local eruption during 2001. Air mass trajectories demonstrated some air parcels were transported over the West Antarctic ice sheet from the Balleny Islands to ice core sites at the time of the potential eruption, establishing a route for transport and deposition of volcanic products over the ice sheet. The data presented here validate previous remote sensing observations and confirms a volcanic event in the Balleny Islands during 2001 CE. This newly identified eruption provides a case study of recent Antarctic volcanism. Key Points: Evidence from ice cores is used to verify a volcanic eruption in the Balleny islands in 2001 CE, supporting evidence from satellites Characterization and timing of microparticles and tephra associated with this eruption provide a chronostratigraphic marker for ice cores